Exploring the causes behind rising food prices in Sub-Saharan Africa - Dejene Gizaw; Øystein Myrland (Cogent Economics & Finance)
This study presents an in-depth analysis of factors affecting the increase and fluctuation of food prices in Sub-Saharan Africa (SSA). It analyses data from 32 countries within the region for the years 2000–2022. Through the application of three-panel regression models, the fixed effects (FEs), a hybrid model and a dynamic model, this research takes a detailed look at factors unique to each country to ensure a comprehensive and accurate examination of the effects. Our results align with both existing theories and prior empirical studies, highlighting the significant roles played by domestic supply shocks, changes in the exchange rate, variations in the money supply from previous periods and the influence of international market trends on food price inflation in SSA. Interestingly, the effect of exchange rate changes and international market influences appears to be waning over time, despite a recent uptick. Additionally, our study points to exchange rate fluctuations as a crucial factor in the instability of food prices.